Regrowth and ornamental traits of bermudagrass fertilized with sewage sludge - Silva, Philippe Solano Toledo [UNESP]; Zabotto, Alessandro Reinaldo [UNESP]; Santos, Patrick Luan Ferreira dos [UNESP]; Nascimento, Matheus Vinícius Leal do [UNESP]; Tavares, Armando Reis; Bôas, Roberto Lyra Villas [UNESP] (FapUNIFESP (SciELO), 2020)
The sewage sludge is a low-cost material and sustainable alternative to substitute chemical fertilizers on ornamental lawns and gardens. Thus, the objective was to evaluate the effects of the application of sewage sludge on the regrowth and ornamental traits of DiscoveryTM bermudagrass. The experiment was carried out during the fall/winter of 2019. The turf was removed and left the soil exposed for a new grass regrowth. The treatments applied were 0, 357, 714, 1,071 and 1,428 g m-2 sewage sludge spread evenly on the lawn in a single dose. The evaluations were carried out after 120 days and the soil solution (EC and NO3-), Normalized difference vegetation index, root length, root + rhizome + stolon + leaves volume and digital image analysis were evaluated. The results showed that the increase of sewage sludge positively influenced the turfgrass development, both in the aesthetic aspect and on bermudagrass regrowth. The soil solution can show that the sludge increased the electrical conductivity and NO3- ions; however, it did not hinder the development of the lawn, even having positive correlations between these variables and the biometric evaluations of the plant. It is concluded that the dose of 1,428 g m-2 presented the best results for the evaluated characteristics, being the recommended one for use in the fertilization of bermudagrass DiscoveryTM.
Keywords: biosolid; organic fertilization; ornamental turfgrass; sod production